The Effect of Auricular and Systemic Acupuncture on the Electromyographic Activity of the Trapezius Muscle with Trigger Points-A Pilot Study - Patrícia Silva de Camargo; Carla Rigo Lima; Maria Luiza de Andrade E Rezende; Adriana Teresa Silva Santos; João Wagner Rodrigues Hernandez; Andréia Maria Silva (Medical Association of Pharmacopuncture Institute, 2018)
The purpose of this study was to analyze and compare intra and intergroup the immediate effect of the auricular and LR8 systemic acupuncture on the electromyographic activity of the trapezius with the trigger points. This is an experimental clinical trial; 40 people were split in 4 distinct groups (n = 10): GI mustard seed application in the auricular acupoint; GII bilateral needle application in the LR8 acupoint; GIII combination of the techniques; GIV/Control Group mustard seed application in an acupoint not linked to the muscle tension. The EMG was used to assess the muscle contraction for 5 seconds during the resting time and during the isometric contraction time. The EMG signal was first collect without the acupuncture intervention; then both techniques were applied for 5 minutes; and the EMG was collected again right after these applications. The Shapiro-Wilk test was used, the t test was paired with the Wilcoxon test to the intragroup comparison; One-way analysis of variance test for intergroup comparison. There was no statistical difference in the intragroup comparison for the groups. The same happened to the intergroup comparison before and after application. Systemic and auricular acupuncture did not promote immediate changes in the EMG activity of the trapezius muscle in individuals with MTrPs.